Nitrogen limitation and slow drying induce desiccation tolerance in conjugating green algae (Zygnematophyceae, Streptophyta) from polar habitats - Pichrtová, Martina; Kulichová, Jana; Holzinger, Andreas (PLoS One, 2014)
BACKGROUND: Filamentous Zygnematophyceae are typical components of algal mats in the polar hydro-terrestrial environment. Under field conditions, they form senescent vegetative cells, designated as pre-akinetes, which are tolerant to desiccation and osmotic stress. KEY FINDINGS: Pre-akinete formation and desiccation tolerance was investigated experimentally under monitored laboratory conditions in four strains of Arctic and Antarctic isolates with vegetative Zygnema sp. morphology. Phylogenetic analyses of rbcL sequences revealed one Arctic strain as genus Zygnemopsis, phylogenetically distant from the closely related Zygnema strains. Algae were cultivated in liquid or on solidified medium (9 weeks), supplemented with or lacking nitrogen. Nitrogen-free cultures (liquid as well as solidified) consisted of well-developed pre-akinetes after this period. Desiccation experiments were performed at three different drying rates (rapid: 10% relative humidity, slow: 86% rh and very slow); viability, effective quantum yield of PS II, visual and ultrastructural changes were monitored. Recovery and viability of pre-akinetes were clearly dependent on the drying rate: slower desiccation led to higher levels of survival. Pre-akinetes survived rapid drying after acclimation by very slow desiccation. CONCLUSIONS: The formation of pre-akinetes in polar Zygnema spp. and Zygnemopsis sp. is induced by nitrogen limitation. Pre-akinetes, modified vegetative cells, rather than specialized stages of the life cycle, can be hardened by mild desiccation stress to survive rapid drying. Naturally hardened pre-akinetes play a key role in stress tolerance and dispersal under the extreme conditions of polar regions, where sexual reproduction and production of dormant stages is largely suppressed.
Keywords: Photosystem II Protein Complex; Antarctic Regions; DNA rostlinná; fylogeneze; transmisní elektronová mikroskopie; Arctic Regions; dusík; Antarktida; Osmotic Pressure; Base Sequence; Desiccation; Streptophyta; Arktida; molekulární sekvence - údaje; Ecosystem; Molecular Sequence Data; sekvence nukleotidů; Microscopy, Electron, Transmission; Nitrogen; osmotický tlak; vysoušení; fotosystém II (proteinový komplex); Phylogeny; ekosystém; Polymerase Chain Reaction; polymerázová řetězová reakce; DNA, Plant